Effect of Motivation on Employees’ Performance in Cooperative Society of Lalitpur Metropolitan City, Nepal - Ballav Niroula; Jitendra Pd. Updhaya (Jambura Science of Management, 2023)
The main objective of this research is to find out effect of motivation on employees’ performance in cooperative institution. In general, the research on effect of motivation on employees’ performance in financial institutions like; commercial banks, insurance companies and cooperative institutions is rarely found in Nepal. Thus, this research tries to explore the impact of motivation on employee’s performance of cooperatives in Nepal. This study is based on descriptive research design. Independent variables on this study are salary and allowance, social security, career development and training facility. The dependent variable on study is employee’s performance. Populations of the study were 329 cooperatives and 30 cooperatives are selected using convenience sampling technique. Data collected through structured questionnaire. Total 230 questions were distributed to the respondent out of which only 193 were used for this study. Five - point Likert scale questions were sent to respondent, where 1= strongly disagree and 5 = strongly agree. Descriptive statistics, correlation and regression analysis are used to analyze the data. Test of reliability has been conducted by using Cronbach’s Alpha. The average value of Cronbach’s Alpha is 0.989 and reliability is acceptable. The study finds that there is a positive and significant effect of career development and training facility on employees’ performance. Salary and allowance have insignificant negative effect and social security has insignificant positive effect on employee’s performance.